Harnessing IgM for solid tumor therapy: biology, engineering advances, and translational challenges - Wang, Yuhui; Wang, Bing; Liu, Shuhan; Chen, Yinuo; Zhang, Shimei; Bu, Lifang; Zhu, Wenjing; Liu, Xinlin; Sun, Peng (Frontiers in Immunology, 2025)
Immunoglobulin M (IgM) antibodies are gaining renewed attention as next-generation platforms for cancer immunotherapy. Compared with IgG, IgM exhibits distinct biological advantages, including higher avidity from multivalent binding, potent complement activation, and enhanced recognition of heterogeneous tumor antigens within immunosuppressive microenvironments. These attributes position IgM as a promising candidate for solid tumor therapy, despite the absence of currently approved IgM-based therapeutics. Recent advances in genetic engineering, antibody design, and protein manufacturing have enabled the generation of diverse IgM formats—ranging from monoclonal and bispecific constructs to engineered IgM derivatives—demonstrating substantial antitumor potential in preclinical and early translational studies. Nonetheless, clinical development faces persistent challenges, including short serum half-life, restricted tumor penetration, structural and biophysical complexity, and scalability of production. In this review, we discuss the structure and biology of IgM, highlight progress in developing novel IgM-based antibody formats for solid tumors, and critically examine the key translational barriers and future opportunities. Together, these insights underscore the therapeutic promise of IgM and chart a path toward its integration into the next generation of antibody-based cancer immunotherapies.